If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + -3) = 2(a + 2) Reorder the terms: 3(-3 + a) = 2(a + 2) (-3 * 3 + a * 3) = 2(a + 2) (-9 + 3a) = 2(a + 2) Reorder the terms: -9 + 3a = 2(2 + a) -9 + 3a = (2 * 2 + a * 2) -9 + 3a = (4 + 2a) Solving -9 + 3a = 4 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -9 + 3a + -2a = 4 + 2a + -2a Combine like terms: 3a + -2a = 1a -9 + 1a = 4 + 2a + -2a Combine like terms: 2a + -2a = 0 -9 + 1a = 4 + 0 -9 + 1a = 4 Add '9' to each side of the equation. -9 + 9 + 1a = 4 + 9 Combine like terms: -9 + 9 = 0 0 + 1a = 4 + 9 1a = 4 + 9 Combine like terms: 4 + 9 = 13 1a = 13 Divide each side by '1'. a = 13 Simplifying a = 13
| 3x+9=3x-27 | | 2(a-3)=2(a+4) | | 0.8-0.6+0.3=5 | | n*2+n-42=0 | | 6x^2-8x-333=0 | | 36x+6=36x+6 | | 3x-2x-6x=-8-2 | | x^2+3x-340=0 | | 25x+110-x=18.50 | | 25b^2-15=0 | | 82=14-6+d | | P(x)=2x^3-6x^2-26x+30 | | 5x^2-64=0 | | x^2+4x-117=0 | | 6m^2-30=0 | | r-12-8+7=27 | | x^2+2x-840=0 | | 2m+1+8m-3=36 | | 25+p=117 | | 4=f/8 | | 12x-108=0 | | 3x+5=8x-10 | | 5x-2y=25 | | -6x+2=3x | | 4(2a-3b)+a-7= | | 159x+75=15 | | x^2-7x-588=0 | | 2x^2+4x-177=0 | | -6y+6=-8y-4 | | g^2-11g-26= | | 2(u-1)+4u=3(u-1)+7 | | 8(w-1)-4=4(2w-3) |